(untitled) (Research, Society and Development, 2022)
The rational use of antimicrobials has been one of the main measures to prevent the increase in antimicrobial resistance in the world. The aim of the present study was to evaluate the use of antimicrobials in a private hospital in Fortaleza/Brazil and to correlate with the increasing antimicrobial resistance. Quantitative data on bacterial infections, microbiological profile and use of antimicrobials were determined, obtained from patients treated in the sectors, between January 2016 and August 2021. 2,733 reports were issued to evaluate the use of antibiotics in 2020 and in 2021 there were 2,044. During 2020, the use of antimicrobials was more frequent between May and June, and in 2021 in March and April, these months reflecting patients with prolonged hospitalization after Covid-19 and multiple secondary bacterial infections. During this period, there is also a greater prescription of Polymyxin B and glycopeptides. When evaluating the Gram-negative sensitivity profile for P. aeruginosa, a drastic reduction in the last year of sensitivity to Piperacillin/tazobactam and Carbapenens, as well as to Polymyxin B (91.7% sensitivity) is observed. For K. pneumoniae, the results were even worse, showing high resistance to Carbapenens and Polymyxin B, whose sensitivity of the latter was only 76.2%, making the choice of therapeutic options difficult. A reduction in sensitivity to Cefatzidime/avibactam was detected for P. aeruginosa, K. pneumoniae and Serratia sp. It was concluded that the increase in the prescription of broad-spectrum antimicrobials during the Covid-19 pandemic may have had an impact on the increase in bacterial resistance, mainly for Gram negatives.